GASTROESOPHAGEAL REFLUX DISEASE IN OBESE PATIENTS - Sattarov, O.T.; Khakimov, I.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Based on the analysis of heart rate variability, the characteristic features of autonomic regulation of the cardiovascular system in patients with gastroesophageal reflux disease, obesity and comorbidity were clarified. For the first time, a comparative characteristic of heart rate variability in patients with different body weights with different endoscopic variants of gastroesophageal reflux disease is given. At the same time, it has been established that the change in heart rate variability in patients is due to the nature of the gastroesophageal zone lesion, the patient’s body mass index and a number of metabolic disorders. For the first time, it has been shown that as the degree of damage to the esophageal mucosa worsens and/or the patient’s body weight increases, there is an increase in blood pressure variability, which is also associated with hyperglycemia. For the first time, cardiovascular risk factors and prognostic formulas for its calculation for patients with gastroesophageal reflux disease, obesity and in case of their combination have been identified.